Black Girls and School Discipline: The Complexities of Being Overrepresented and Understudied. (February 2019) - Annamma, Subini Ancy; Anyon, Yolanda; Joseph, Nicole M.; Farrar, Jordan; Greer, Eldridge; Downing, Barbara; Simmons, John
Using Critical Race Theory and Critical Race Feminism as guiding conceptual frameworks, this mixed-methods empirical study examines Black girls' exclusionary discipline outcomes. First, we examined disciplinary data from a large urban school district to assess racial group differences in office referral reasons and disparities for Black girls in out-of-school suspensions, law enforcement referrals, and expulsions. Next, we used a multivariate analysis to determine whether these patterns held after accounting for other identity markers. Finally, we used Critical Discourse Analysis to consider whether office referrals for Black girls were for subjective or objective behaviors and whether they aligned with dominant narratives.